2017
DOI: 10.1007/s12011-017-1186-9
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Selenium on the Chicken Pancreas against Cadmium Toxicity via Alleviating Oxidative Stress and Autophagy

Abstract: Cadmium (Cd) is a highly toxic heavy metal that can affect human and animal health. Selenium (Se) is an essential microelement that can protect various organs against toxic heavy metals. Although many studies have investigated the adverse effect of Cd in rats and several other animals, little is known regarding the mechanisms of Cd-induced autophagy in the chicken pancreas and the antagonistic effect of Se on Cd. In the current study, we fed chickens Se, Cd, or Se and Cd supplements to establish the Se and Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Se was reported by one of the articles to alleviate spleen toxicity in a chicken model induced by Pb via the modulation of oxidative stress, in ammation, and autophagy [12]. Se alleviated protein increase of ATG5, Beclin1, Dynein, LC3-I, and LC3-II and protein decrease of mTOR in Cd-induced chicken pancreas [58]. In our study, all alterations caused by Pb were ameliorated by treatment with Se.…”
Section: Discussionsupporting
confidence: 63%
“…Se was reported by one of the articles to alleviate spleen toxicity in a chicken model induced by Pb via the modulation of oxidative stress, in ammation, and autophagy [12]. Se alleviated protein increase of ATG5, Beclin1, Dynein, LC3-I, and LC3-II and protein decrease of mTOR in Cd-induced chicken pancreas [58]. In our study, all alterations caused by Pb were ameliorated by treatment with Se.…”
Section: Discussionsupporting
confidence: 63%
“…Secondly, the Cd content of organs was not determined. Several studies reported that the pancreas is one of the target organs of Cd and Cd exposure produced a time-dependent Cd accumulation in the pancreas [16, 30, 31]. Substantial Cd concentration in the pancreas in present long-term Cd exposure study is speculated.…”
Section: Discussionmentioning
confidence: 69%
“…Cd exposure could trigger significant increase in blood glucose concentration and lipid peroxidation and significant decrease in body weight, blood insulin level, GSH, and activity of antioxidant enzymes in pancreatic tissue [45]. Liu [46] found that Cd concentration and MDA content were elevated and antioxidant activity markers (CAT, SOD, GSH-Px, and T-AOC) were decreased in pancreas of chickens exposed to Cd. Similarly, Cd treatment elevated the MDA concentration and decreased levels of GSH, SOD, and CAT in male Wistar albino rats [47].…”
Section: Discussionmentioning
confidence: 99%